Fatigue life of underwater wet welded low carbon steel SS400. Issue 2 (February 2020) - Muhayat, N.; Matien, Y.A.; Sukanto, H.; Saputro, Y.C.N.; Triyono,
Abstract: Underwater welding is widely used for maintenance and repairs of underwater structures such as undersea pipes, offshore structures and nuclear power plants. In practice, underwater welding has the disadvantage related to high cooling rate and unstable welding arc due to the water hydrostatic pressure. This affects the microstructure and mechanical properties of underwater welded joints. Many of previous research works on underwater welding have been carried out only on a laboratory scale in shallow water depth, whereas underwater welding was used to weld in the depth of the water with a metre scale. Undersea structures experience fatigue load due to the fluctuation force of water flow. Therefore, this study aims to determine the effect of water depth on the fatigue life of underwater welded joints. Low carbon steel SS400 specimens were welded underwater with depths of 2.5 m, 5 m and 10 m. The air welded joint was also evaluated for comparison purposes. Fatigue life was evaluated according to the ASTM E466 standard by using a rotary bending machine. Furthermore, tensile test, micro hardness measurement and microstructure evaluation were also conducted for gathering supporting data. The fatigue and tensile strength of the air welded joints were higher than those of the underwater welded joints. The porosities caused by the dissolved hydrogen gas, carbon (monoxide and dioxide) gases and water vapor in weld metal of the underwater welded joints decreased the fatigue and tensile strength. An interesting phenomenon on the underwater welded joints was that the deeper the water level, the higher became the fatigue, tensile strength as well as hardness. Based on the microstructure analysis, the number of acicular ferrite structures in weld metal increased as the water level depth increased. Abstract : Materials science, Mechanical engineering, Underwater, Wet welding, Fatigue life, Low carbon steel, Water depth, Acicular ferrite.